Specialist Networks Influence Clinician Willingness to Treat Individuals with Special Needs. (July 2022) - Lim, M.A.W.T.; Liberali, S.A.C.; Calache, H.; Parashos, P.; Borromeo, G.L.
Background: The South Australian Dental Service's Special Needs Network was established to support oral health professionals working within their statewide government-funded dental service to treat patients with special needs. This study aimed to investigate how a structured network relationship with specialists in special needs dentistry influenced the willingness of dentists to treat this group of patients. Methods: Semi-structured interviews were used to explore the views of specialists and dentists involved in the South Australian Dental Service's Special Needs Network. Inductive thematic analysis identified emerging themes enabling completion of a SWOT (strengths, weaknesses, opportunities, threats) analysis. Results: Dentists felt that a strength of the Network was a greater sense of collegiality, particularly for those working in rural areas. Although the inability to get immediate advice was seen as a weakness, dentists felt a more structured relationship with specialists improved communication pathways and resulted in more timely care. The aging workforce, systemic barriers in the public dental system, such as productivity pressures and infrastructure, and the lack of support from other health professionals were seen as ongoing barriers and threats. Regardless, dentists identified the use of telehealth and visiting specialists as future opportunities. Specialists felt that the Network was a valuable resource but were skeptical about its effectiveness, feeling that a limitation was the ability of dentists to recognize the complexity of cases. Conclusions: Ongoing support from and communication with specialists in special needs dentistry through a structured network improved the perceived ability and willingness of dentists to treat patients with special needs. Knowledge Transfer Statement: This research suggests that providing support to dentists through a hub-and-spoke network that facilitates additional training, professional interaction, and improved communication with specialists in special needs dentistry may help overcome some of the current barriers to access to care experienced by individuals with special needs, particularly those associated with the willingness and capability of clinicians treat them.